A Randomized Clinical Trial of Linagliptin vs. Standard of Care in Patients Hospitalized With Diabetes and COVID-19 - Abuhasira, Ran; Ayalon-Dangur, Irit; Zaslavsky, Neta; Koren, Ronit; Keller, Mally; Dicker, Dror; Grossman, Alon (Frontiers in Endocrinology, 2021)
Objective: To assess the effect of linagliptin vs. standard therapy in improving clinical outcome in patients hospitalized with diabetes and coronavirus disease 2019 (COVID-19) Pneumonia. Materials and Methods: We did an open label, prospective, multicenter, randomized clinical trial in 3 Israeli hospitals between October 1, 2020, and April 4, 2021. Eligible patients were adults with type 2 diabetes mellitus and a diagnosis of COVID-19. A total of 64 patients, 32 in each group, were randomized to receive linagliptin 5 mg PO daily throughout the hospitalization or standard of care therapy. The primary outcome was time to clinical improvement within 28 days after randomization, defined as 2-point reduction on an ordinal scale ranging from 1 (discharged without disease) to 8 (death). Results: The mean age was 67±14 years, and most patients were male (59.4%). Median time to clinical improvement was 7 days (IQR 3.5-15) in the linagliptin group compared to 8 days (IQR 3.5-28) in the standard of care group (hazard ratio, 1.22; 95% CI, 0.70-2.15; P=0.49). In-hospital mortality was 5 (15.6%) and 8 (25.0%) in the linagliptin and standard of care group, respectively (odds ratio, 0.56; 95% CI, 0.16-1.93). The trial was prematurely terminated due to the control of the COVID-19 outbreak in Israel. Conclusions: In this randomized clinical trial of hospitalized adult patients with diabetes and COVID-19 who received linagliptin, there was no difference in the time to clinical improvement compared with standard of care.